Design and fabrication of height adjustable study table / Haikal Hakimi and Nurulsaidatulsyida Sulong - Hakimi, Haikal; Sulong, Nurulsaidatulsyida (School of Mechanical Engineering, 2023)
Student nowadays sit at desks longer than they used to do something else. Either they do study in the morning at school or university or in the afternoons at home to do homework, to read, do handicrafts and to play games. No wonder that more and more students or children are complaining about their health problems, back pain, and muscle tension. Due to these problems, a height adjustable study table was fabricated. Hollow steels were cut and weld to produce table frame with two actuators inside the steels and chipboard was used as the tabletop. Minimum height for this table is 80cm and maximum height for this table can up to 1.2 meters. Therefore, a height adjustable table was successfully fabricated and can give numerous benefits to the users to prevent from backpain and others health problem.